2008
DOI: 10.1007/s00412-008-0168-2
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional positioning of genes in mouse cell nuclei

Abstract: To understand the regulation of the genome, it is necessary to understand its three-dimensional organization in the nucleus. We investigated the positioning of eight gene loci on four different chromosomes, including the β-globin gene, in mouse embryonic stem cells and in in vitro differentiated macrophages by fluorescence in situ hybridization on structurally preserved nuclei, confocal microscopy, and 3D quantitative image analysis. We found that gene loci on the same chromosome can significantly differ from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 71 publications
3
38
0
Order By: Relevance
“…The correlation coefficient (R) value in the figure was calculated to be -0.62. This value is comparable to those reported in the above cited study, in which the R values were almost the same between the ES cells and macrophages, -0.61 and -0.63, respectively (Hepperger et al, 2008). Our study showed that in hepatocytes, gene localization correlated very well with not only the local GC content but also gene density, and the R value of the former was -0.92 ( Figure 3D) and that of the latter -0.71 ( Figure 3B).…”
Section: Gene Localization Is Highly Dependent On Gc Content In Hepatsupporting
confidence: 90%
See 4 more Smart Citations
“…The correlation coefficient (R) value in the figure was calculated to be -0.62. This value is comparable to those reported in the above cited study, in which the R values were almost the same between the ES cells and macrophages, -0.61 and -0.63, respectively (Hepperger et al, 2008). Our study showed that in hepatocytes, gene localization correlated very well with not only the local GC content but also gene density, and the R value of the former was -0.92 ( Figure 3D) and that of the latter -0.71 ( Figure 3B).…”
Section: Gene Localization Is Highly Dependent On Gc Content In Hepatsupporting
confidence: 90%
“…Gene localization is reportedly correlated with some genomic properties (Murmann et al, 2005;Hepperger et al, 2008;Jost et al, 2011). Therefore, we examined whether such a correlation exists for the genes under analysis.…”
Section: Relationship Between Gene Position Gene Density and Gc Contentmentioning
confidence: 98%
See 3 more Smart Citations